The Antônio Conselheiro Settlement: The Importance of the Collective Map in Reading Peasant Reality - Alexandra Maria de Oliveira; Antônia Sandra Honoria de Sousa; Grasiele Ribeiro (Universidade Federal do Norte do Tocantins, 2021)
The conquest of rural settlements in the Brazilian countryside has led to the certainty of new daily challenges for the settlers, including the struggle for public policies that boost production, income generation, and good quality education. The article aims to analyze the use of social cartography in the Antônio Conselheiro Settlement, located between Ocara and Aracoiaba in Ceará, Brazil. The methodological procedure is part of a research project carried out between 2016 and 2018 and was developed based on pedagogical workshops conducted with students of the Education Service for Youth and Adult Rural Workers (EJA) at Raimundo Facó School. Additionally, fieldwork, interviews, preliminary sketches, and the collective map were used in the research. This Social cartography was developed at a time when the communities were experiencing conflict with public agencies and looking for ways to demonstrate their work and autonomy in the management of spaces for production, marketing, and leisure. The results show a consolidated rural settlement with the production, consumption, and commercialization of agricultural and artisanal products. The introduction of social cartography to the community through adult elementary education is a differentiated approach to the dialogue between popular and geographic knowledge and is fundamental for interpreting the peasant reality.